DISTRAKSI VISUAL VIDEO ANIMASI DAN VIRTUAL REALITY DALAM MENGURANGI KECEMASAN ANAK USIA 7-10 TAHUN PADA TINDAKAN ANESTESI INFILTRASI - Ika Anisyah Lubis; Witriana Latifa Wibisono; Rini Triani Sjamsul; Roosje Rosita Oewen (Universitas Baiturrahmah, 2021)
Introduction: Dental practitioners have numerous methods to control anxiety and pain in children, and distracting the child appears to be the most command technique used for behavior management during dental procedures. The audiovisual technique is used as a distraction method for reducing anxiety. This study aimed to compare the efficacy of using an audiovisual animation video and virtual reality distraction toward anxiety alteration on children age 7-10 years old on infiltration anesthesia. Method: The design of this study was pretest and post-test, thirty-two children were divided into two groups namely animation video group (n=16) and virtual reality groups distraction (n=16). Result: The efficacy of animation video distraction by 48,9% while using virtual reality is 43,75%. Data analysis using an independent t-test which results in a p-value less than 0,05 in which it was showed non-significant differences between the two groups. Conclusion: The two methods of distraction both animation video and virtual reality have the same effect on reducing anxiety in children age 7-10 years old on filtration anesthesia.